PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SUBTEMA BANGGA TERHADAP DAERAH TEMPAT TINGGALKU - Amalia, Intan; Muhajang, Tatang; Hikmah, Nur (Jurnal PGSD, 2023)
This research is a quasi-experimental research. This study aims to determine the effect of the Problem Based Learning model on the learning outcomes of the proud sub-theme of the area where I live. This research was conducted at the Cimanggis 02 Public Elementary School, Bogor district, Class IV A, and IV B from May to even semesters. The N-Gain calculation of the Problem Based Learning models is 70 with high criteria and 83% completeness oh learning outcomes, the N-Gain value of the conventional model is 37 with medium criteria and 70% completeness of learning outcomes. The results of hypothesis testing state that H0 is rejected and Ha is accepted, because the calculation results are tcount (5,8718) > ttable (2,00172). Based on the results of the study, it was concluded that there was an influence from the use of the Problem Based Learning model on the learning outcomes of the proud sub-theme of the area where I live. A very effective learning model to be used in the sub-theme of being proud of the area where I live is the Problem Based Learning model.